Pengaruh Risiko Bisnis, Profitabilitas, dan Keputusan Investasi terhadap Struktur Modal - Putri Pertiwi, Ni Wayan Aditya; Artini, Luh Gede Sri (E-Jurnal Manajemen, 2014)
Capitalkstructure is the balance betweenlthe use of their own with,the use of debt capital . Given the many factors that affect the capital structure , but the variables used in this study , namely , business risk , profitability , investment decisions on capital structure of the company Property and Real Estate sectors . The purpose of the study to examine and determine the effect of business risk , profitability , and investment decisions of the firm's capital structure on the property and real estate sector are listed on the BEI in the period 2009-2011. The method used was purposive sampling is a sampling method taking an object with the specified criteria . The number of samples in accordance with the criteria that have been determined a total of 36 real estate companies and property in BEI . Analysis of data using multiple regression analysis tool test results found  business risk , Profitability  and invesment decision partially influential and significant impact on thepcapital structure. Keyword: business risk, profitability,  investment decisions, capital structure